The prognostic predictors of patients with airway involvement due to advanced esophageal cancer after metallic airway stenting using flexible bronchoscopy - Cheng, Wen-Chien (J Thorac Dis, 2019)
BACKGROUND: Patients with advanced esophageal cancer and airway involvement have a poor prognosis. Self-expandable metallic stent (SEMS) implantation via bronchoscopy can immediately relieve airway stenosis and improve survival. The purpose of this study was to determine the factors that predict survival in patients with airway involvement due to advanced esophageal cancer after SEMS implantation. METHODS: We conducted this retrospective study from February 2007 to October 2013 at a university hospital. Forty-two patients with advanced esophageal cancer and airway involvement were included. The patients underwent flexible bronchoscopy with electrosurgery and SEMS implantation under bronchoscopic visualization and local anesthesia with no fluoroscopic guidance throughout the procedure. RESULTS: Acute respiratory failure (ARF) occurred in 14 patients (33.3%). After SEMS implantation, 28 patients (66.7%) received additional anti-cancer therapy. The median survival after the procedure was 83 days. A longer survival was seen in the patients who received further anti-cancer therapy [hazard ratio (HR), 0.146; 95% confidence interval (CI), 0.06–0.34; P<0.001]. Persistent pneumonia and poor performance status (PS) were potential factors for not receiving further therapy. The patients who received anti-cancer therapy before the procedure (HR, 3.429; 95% CI, 1.54–7.60; P=0.002) and those with ARF (HR, 5.224; 95% CI, 2.23–12.26; P<0.001) had worse survival. CONCLUSIONS: SEMS insertion with flexible bronchoscopy without fluoroscopic guidance in the patients with airway involvement due to advanced esophageal cancer was safe and feasible. The patients who received anti-cancer therapy before the procedure and those with ARF had a poor prognosis. Post-airway stenting therapy had the positive impact on survival in these patients.